The Resurgence of Singular Identities: Possible Explanations. Issue 2 (3rd April 2019) - Kaldor, Mary
Abstract: This article is a reflection on Sen's book Identity and Violence and its relevance in explaining the rise of sectarian narratives world-wide. It makes three arguments. First what Sen calls "singular" or "unidimensional" identities, which tend to be binary or "either/or" identities, are not merely a determinant of violence, as Sen argues, but also an outcome of violence setting in motion a self-reinforcing logic. Second the rise of singular identities is associated with top-down authoritarian regimes who manipulate identity as a way of deflecting democratic pressures. Thirdly the contemporary rise of singular identities can be explained in terms of the spread of what is known as globalisation, including growing interconnectedness that broken down the congruence between the state and the economy, new forms of communication including social media that are more conducive to fragmentary horizontal identities than was the traditional media associated with print and television, and thirdly the increasing reliance on rent as a source of revenue for many states that weakens the social contract between state and citizen. The article concludes that these tendencies are not inevitable and it is possible to envisage the emergence of "both/and" identities that could underpin a lyering of global governance.